2013
DOI: 10.1007/s12199-013-0342-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of health-promoting lifestyles on the quality of life of retired workers in a medium-sized city of Northeastern China

Abstract: Objectives The aim of this study was to clarify the actual state of retired workers' lifestyles and quality of life (QOL) in a medium-sized city of Northeastern China and to assess the relationship between these according to differences between gender groups. Methods The Chinese version of the Health Promotion Lifestyle Profile II (HPLP-II), the World Health Organization Quality of Life-BREF (WHOQOL-BREF), and demographic variables were used to measure 343 (aged 50-79 years) retired workers' lifestyles and QOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 39 publications
9
24
0
Order By: Relevance
“…However, there is a dearth of research on the effect of self-care activities in later life. Only a handful of recent studies empirically examined the effect of self-care activities in later life and found the positive relationship between self-care activities and quality of life among female adults in Hong Kong (Mo and Winnie 2010) and among older adults in China (Zhang et al 2013). With a large number of young-old adults entering later life, it is critical to understand their LTC needs in South Korea.…”
Section: Factors Affecting Intention To Use Ltc Facilitiesmentioning
confidence: 99%
“…However, there is a dearth of research on the effect of self-care activities in later life. Only a handful of recent studies empirically examined the effect of self-care activities in later life and found the positive relationship between self-care activities and quality of life among female adults in Hong Kong (Mo and Winnie 2010) and among older adults in China (Zhang et al 2013). With a large number of young-old adults entering later life, it is critical to understand their LTC needs in South Korea.…”
Section: Factors Affecting Intention To Use Ltc Facilitiesmentioning
confidence: 99%
“…Since the initial health promotion conference in 1986 there has been a global public health movement on health promotion (Sonmezer, Cetinkaya, & Nacar, 2012). The premise for this movement is that as people engage actively in health-promoting lifestyle practices they enjoy a good quality of life (Sonmezer et al, 2012;Zhang, Tao, Ueda, Wei, & Fang, 2013;Mokdad, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A healthy lifestyle involves all the efforts an individual makes to promote health and to prevent illness (Sonmezer et al, 2012). Literature revealed an increase in morbidity and mortality rates associated with NCDs (Shehu, Onasanya, Onigbinde, Ogunsakin, & Baba, 2013;Zhang et al, 2013;Casey et al, 2014;Mokdad, 2016). However, health-promoting lifestyle has been identified as a means of preventing the risk and complications associated with the diseases as well as their onset (Fang-Hsin & Hsiu-Hung, 2005;Zhang et al, 2013;Ryu, Park, Choi, & Han, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations